EFFECT OF SILVER NANOPARTICLES IN EXPERIMENTAL PERITONITIS - D. V. Chegodar; A. V. Kubyshkin; V. V. Panasenko (Бюллетень сибирской медицины)
In our research we have investigated the effect of intraperitoneal introduction of silver nanoparticles solution (linear particle size of 10–20 nm) into intact animals and in the simulation of experimental peritonitis. We have evaluated the indices of nonspecific proteinases and their inhibitors in blood serum and peritoneum lavage. The intraperitoneal introduction of silver nanoparticles solution to intact animals leads to the minimal reaction of proteinase-inhibitor systems components in blood serum and peritoneum lavage. When modeling inflammatory process in peritoneum cavity by intraperitoneal injection of 10% filtered fecal suspension of rats, application of silver nanoparticles solution is accompanied by decrease in extent of activation of proteinases and preservation of inhibitory potential, both at systemic and local level, which can indicate antiinflammatory effects of nanosilver.